The Nigerian Diaspora’s Contributions to the Development of Higher Education - Wapmuk, Sharkdam (International Journal of African Higher Education, 2021)
While engagement with the Nigerian diaspora has focused on attracting investment and remittances, recently, attention has also shifted to its contribution to the development of higher education. The descriptive and qualitative study on which this article is based drew on secondary data that was analysed through content analysis. The findings revealed that a combination of factors motivated Nigerians, including intellectuals, to emigrate, particularly in the 1980s and 1990s. This compounded existing problems in Nigeria’s higher education sector. Since 1999, successive governments have engaged the diaspora in national development, including higher education. The study found that through the Linkages with Experts and Academics in the Diaspora Scheme, the United Nations Development Programme’s Transfer of Knowledge Through Expatriate Nationals, and the World Bank assisted Nelson Mandela Institution, known as the African University of Science and Technology, as well as alumni associations in the diaspora, Nigerian diaspora academics have been returning home to transfer knowledge in universities. Other contributions include projects, donations, and programmes. However, several challenges constrain the tapping of their full potential. The article recommends that the Nigerian government should create an enabling environment, ensure clarity of expectations, provide adequate funding and adopt long-term approaches to engage with the Nigerian academic diaspora. Key Words: Nigerian diaspora, higher education, brain-drain, brain-gain, knowledge transfer